Nitrate and potassium concentrations in cotton petiole extracts as influenced by nitrogen fertilization, sampling date and cultivar - López, M.; Castro, A. de; Gutiérrez, J.C.; Leidi, E.O. (Spanish Journal of Agricultural Research, 2010)
The effect of nitrogen fertilization levels on seed cotton yield responses of cultivars from Andalusia was studied during two consecutive years. To obtain preliminary information for improving nutrient management, the analysis of nitrate and potassium (K) was performed in petiole extracts at critical times (flowering, boll-setting, boll growth) during the growth cycle. Signif icant differences among cotton cultivars were found for petiole nitrate and K concentrations. The highest petiole nitrate and K concentrations were found in cultivar "Crema 111" with 4.140 and 14.180 mg/kg respectively. These concentrations were affected by N treatment and sampling date. The relationships among petiole nutrient concentrations and seed cotton yield depended on sampling date, cultivar and year. The highest association between petiole nitrate and yield was found early in the season in 2003 (r = 0.918 and r = 0.965 for "Crema 111" and "Sor Angela" respectively). The analysis of petiole extracts for controlling plant nutritional status and optimize seed cotton yield requires a systematic assessment as critical values in nutrient concentration for seed cotton yield may differ depending on cultivar, soil type, sampling date and crop management. The technique of petiole analysis used in this paper might be useful for detecting genotypes with improved nutrient uptake or use efficiency.